The Use of Neutron Analysis Techniques for Detecting The Concentration And Distribution of Chloride Ions in Archaeological Iron. (17th October 2013) - Watkinson, D.; Rimmer, M.; Kasztovszky, Z.; Kis, Z.; Maróti, B.; Szentmiklósi, L.
<x xml:space="preserve">Abstract</x> Chloride (Cl) ions diffuse into iron objects during burial and drive corrosion after excavation. Located under corrosion layers, Cl is inaccessible to many analytical techniques. Neutron analysis offers non‐destructive avenues for determining Cl content and distribution in objects. A pilot study used prompt gamma activation analysis (PGAA) and prompt gamma activation imaging (PGAI) to analyse the bulk concentration and longitudinal distribution of Cl in archaeological iron objects. This correlated with the object corrosion rate measured by oxygen consumption, and compared well with Cl measurement using a specific ion meter. High‐Cl areas were linked with visible damage to the corrosion layers and attack of the iron core. Neutron techniques have significant advantages in the analysis of archaeological metals, including penetration depth and low detection limits.